Identity and Historical Amnesia in an Event Culture – on Function and Failure of 'Memory Movies' (KULT_online, 2013)
While analyses of individual history and memory movies have become quite popular in recent years, in-depth methodical approaches to the field of film and memory studies are still rare. With his dissertation, Gerhard Lüdeker means to fill this gap and, thus, conducts a systematical analysis of memory movies focusing on two outstanding collective memory discourses in twentieth-century Germany: the Nazi period and the Fall of the Wall leading to the reunification of the two German states.In the first part, the author elaborates well-known theoretical concepts of collective identity and media of collective memory in detail, and, in consequence, does not significantly enhance the field of film and memory studies. The work culminates in cultural pessimism about contemporary society, which, in his opinion, only offers ahistorical identity concepts. However, Lüdeker offers thorough film analyses that point to an increasing discourse of normalization, detectable in recent movies on the Nazi and reunification periods.